Design of an on-board charger for plug-in hybrid electrical vehicle (PHEV) - Grenier, Mathieu (My University, 2009)
The purpose of this project is to design an on‐board charger with the aim of charging a plugin vehicle battery. This charger is able to control the values of the load voltage and current and then, maintain them at a desirable value. A first converter is used to transform the grid 50Hz electrical quantities into DC quantities. A second converter adjusts the levels to the values required by the battery and moreover, provides a galvanic isolation. The control of the first converter is realized by using a power factor corrector function. The control of the second converter allows supplying the battery with correct voltage and current values. This method is one of the most efficient to design an electronic supply with a low current harmonic impact to the grid. This converter topology is investigated in this report. The choice of the structure and the choice of the components are explained, the magnetic components, inductors and transformer, are designed. A simulation, realized in Matlab Simulink, allows the understanding of the working principle of the power factor corrector and the full bridge converter. Simulations allow checking the theory part and the determination of the problems occurring in the on‐board charger. The efficiency of the on‐board charger is also determined with Matlab. Determination of the loading cost and loading time needed is investigated.
Keywords: Elkraftteknik; Electric power engineering